Sustainability of Bangalore software industry : a qualitative study - Komarlingam Narayanan Suresh (2008)
The dissertation looks at the Bangalore story so far, noting the path it has taken form humble beginnings to get to where it is today. It then analyzes data and discusses the Critical Success Factors and key issues pertaining to infrastructure, human resource, economics, technology and competitive strategy.